The effect of genotype and ecological conditions on the yield components of potatoes - Poštić Dobrivoj; Momirović Nebojša; Broćić Zoran; Đukanović Lana; Štrbanović Ratibor; Terzić Dragan; Stanisavljević Rade (Journal on Processing and Energy in Agriculture, 2017)
The research on the effect of ecological conditions and cultivars on the yield components of potatoes was conducted in Badovinci (Western Serbia) during the period 2008-2009. The following potato cultivars were included in the experiment: early ('Cleopatra', 'Anushka' and 'Presto'), medium early ('Kuroda', 'Omega' and 'Dita'), and medium late ('Desiree', 'Roko' and 'Jelly'). The four-replicate field trials were set up using the standard methodology according to the random block design. 18TThe research results suggest that genotype (G) and ecological conditions (E) significantly affect all yield components of potatoes. In both years, the highest yield was recorded18T in18T the medium late variety 'Desiree'18T 18T(18T28.30 t ha־¹), followed by the early variety 'Anushka' 18T(18T26.60 t ha־¹), 18Twhile the lowest18T 18Tyield18T was 18Trecorded18T 18Tin the medium early variety 'Omega' (18T13.35 t ha־¹). The 18Tresults obtained show that18T 18Tthe18T 18Thighest yields18T in Western Serbia were 18Trecorded in early varieties18T 18T('Cleopatra'18T, 'Anushka' 18Tand18T '18TPresto'18T) and 18Tmedium18T 18Tlate varieties18T 18T('18TDesiree'), which exhibited considerable18T resistance to high18T 18Tair temperatures18T and 18Tdrought stress18T.